Supervisory practices of student teaching in some selected public regional normal schools in the Philippines - Flores, Purificacion M. 1932- (s.n.], 1966)
This study described the supervisory practices of student teaching in selected public normal schools in the Philippines. This includes the following identifiable supervisory practices of student teaching both on-campus and off-campus in selected public normal schools: practices regarding assignment, practices regarding orientation and guidance, and the practices regarding evaluation.